2015
DOI: 10.1016/j.biopsych.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Diversity of Corpus Callosum and Brain Volume in Autism: Meta-analysis, Analysis of the Autism Brain Imaging Data Exchange Project, and Simulation

Abstract: The lack of statistical power in the previous literature prevents us from establishing the reality of the claims of a smaller CC in autism, and our own analyses did not find any. However, the nonlinear relationship between CC and BV and the different correlation between BV and IQ in cases and control subjects may induce artifactual differences. Overall, our results highlight the necessity for open data sharing to provide a more solid ground for the discovery of neuroimaging biomarkers within the context of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 46 publications
4
108
1
4
Order By: Relevance
“…By contrast, Lefebvre et al (2015) found no difference in corpus callosum size in their sample of 694 individuals with ASD compared to TD controls. Studies of the amygdala in ASD have reported significantly Bincreased, decreased and preserved volumes^of the amygdala (Bellani et al 2013, p. 3).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 94%
See 2 more Smart Citations
“…By contrast, Lefebvre et al (2015) found no difference in corpus callosum size in their sample of 694 individuals with ASD compared to TD controls. Studies of the amygdala in ASD have reported significantly Bincreased, decreased and preserved volumes^of the amygdala (Bellani et al 2013, p. 3).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 94%
“…However, in other studies, approximately 10 to 24 % of individuals diagnosed with ASD had persisting macrocephaly (Gillberg and de Souza 2002;Lainhart 2015;Nebel et al 2015;Sacco et al 2015;Tammimies et al 2015). In addition, a number of studies have reported that 3 to 15 % of individuals with ASD had persisting microcephaly (Gillberg and de Souza 2002;Nebel et al 2015;Roullet et al 2013;Stevens et al 2013).Although Riddle et al (2016) found no regional brain differences in 443 individuals with ASD compared to 390 TD individuals, Lefebvre et al (2015) noted that many studies had found significantly smaller corpus callosum in ASD than TD controls. By contrast, Lefebvre et al (2015) found no difference in corpus callosum size in their sample of 694 individuals with ASD compared to TD controls.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The inconsistencies in findings are likely primarily due to the small sample sizes used in most studies, in combination with the large behavioural heterogeneity, as well as measurement related differences (Auzias et al, 2014(Auzias et al, , 2016Castrillon et al, 2014). Thus, there is an urgent need for larger sample sizes, if we are to discover clinically useful information (Amaral et al, 2008;Auzias et al, 2014Auzias et al, , 2016Lefebvre et al, 2015). Large samples may allow the extraction of core neuroanatomical abnormalities from the noise introduced by the heterogeneity of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…29 Future investigations into population norms will also be important when considering the large phenotypic diversity of the brain in ASD, which can only be reliably interpreted in the context of the wide neuroanatomical diversity within the general population. 30 Evidence also suggests that early brain overgrowth in ASD is not restricted to the brain exclusively, but that early generalised patterns of physical (ie, somatic) overgrowth occur in ASD, particularly in boys. 31,32 Thus, dynamic changes in population norms and factors responsible for both neural and non-neural tissue development should be considered to provide a more comprehensive assessment of atypical brain development in ASD.…”
Section: Atypical Brain Development Early Brain Developmentmentioning
confidence: 99%